Acceptance of oral chemotherapy in breast cancer patients: a survey study - Schott, Sarah; Schneeweiss, Andreas; Reinhardt-Klötzke, Judith; Bruckner, Thomas; Domschke, Christoph; Sohn, Christof; Eichbaum, Michael H. R. (BMC cancer, 2011)
Oral (p.o.) chemotherapy treatments gained increasing importance in the palliative treatment of metastatic breast cancer (MBC). Aim of this survey was to evaluate the acceptance of p.o. treatment and patients' individual attitudes towards it.
Gesehen am 26.10.2022